Plyometrics - Chu, D. A.; Myer, G. D. (Human Kinetics, 2013)
Strength and power—which provide the ability to move quickly with great force—are absolute necessities for today's athletes. Elite players, coaches, and trainers rely on plyometrics to improve quickness, speed, jumping ability, footwork, body control, balance, and overall performance. With this authoritative guide on plyometrics, you can, too.